1274 Impact of Covid 19 on Urgent Suspicion of GI Cancer Referral in a District General Hospital. (12th October 2021) - Barman, S; Ng, H J; Teo, S; Blaney, E M; Mansfield, O
Abstract: Aim: Endoscopy services across United Kingdom were affected significantly since March 2020 due to Covid-19 pandemic. Services were reduced and were more selective. We aim to compare the impact on duration between referral to colonoscopy and the detection rate of pathology between February (pre- Covid) and August (Covid impacted) 2020. Method: Data was analysed from a prospectively maintained database of patients referred for colonoscopy to Royal Alexandra Hospital, Scotland. Patients underwent colonoscopy in month of February and August 2020 were included. Bowel screening patients were excluded. Positive findings included diverticulosis, colitis, polyp and adenocarcinoma. P value of < 0.05 was considered significant. Results: Total number of patients included was 97 (55 in February, 42 in August). Median age was 61 and 69 years, respectively. Mean duration from referral to colonoscopy were 4 weeks in February and 7 weeks in August. qFIT test were found raised in 50.9% in February and 57.1% in August with positive findings of 47.3% in February and 66.7% in August. 46.4% in February and 16.7% in August had raised qFIT but normal findings (p < 0.05). Two high grade dysplasia polyps and two adenocarcinomas were identified in February, none found in August. Conclusions: Covid-19 pandemic has disrupted the endoscopic services prolonging the duration from referral to colonoscopy. qFIT test is more heavily relied to prioritise urgent colonoscopies resulting in more positive findings on colonoscopy. Cancer detection rate has reduced which is a consistent finding as the UK national endoscopy study. Massive efforts are needed to restore endoscopy services.